1965
DOI: 10.1071/ph650059
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Proton Flux with Atmospheric Depth Between 10 and 50 g/cm2 at l = 47° S. Geomagnetic

Abstract: SummaryProton fluxes at atmospheric depths between 10 and 50 g/cm2 have been measured using nuclear emulsions during a series of balloon flights over Melbourne (A = 47° S. geomagnetic) in the period November 1961-April 1962. The proton flux J(x) decreases with increasing depth within this region. It can be represented by the relation log J(x) = (3·05±0·02)-(2·36±0·66)xlO-3x and, when extrapolated, gives the flux at the top of the atmosphere to be 1120±50 protons m-2 steradian-1 S-l.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…The average transverse momentum in events with multiple minijets is certainly larger than those without, thus leading to the increase of p T with n ch . In order to understand the different behavior of the correlations between p T and n ch for different particles, we recall that the jet fragmentation functions for heavy hadrons tend to be harder than for light hadrons, as measured in e + e − annihilation experiments [80]. Therefore, heavy hadrons from jet fragmentation carry larger transverse momenta than light hadrons in [69,70].…”
Section: Minijets and Transverse Flowmentioning
confidence: 99%
“…The average transverse momentum in events with multiple minijets is certainly larger than those without, thus leading to the increase of p T with n ch . In order to understand the different behavior of the correlations between p T and n ch for different particles, we recall that the jet fragmentation functions for heavy hadrons tend to be harder than for light hadrons, as measured in e + e − annihilation experiments [80]. Therefore, heavy hadrons from jet fragmentation carry larger transverse momenta than light hadrons in [69,70].…”
Section: Minijets and Transverse Flowmentioning
confidence: 99%
“…The resulting average multiplicity of charged hadrons as it rises with Q is shown in Fig. 13a together with experimental data [45,46]. In order to obtain the correct overall normalization, we fitted the the infrared regulator k 0 entering α s , eq.…”
Section: Cluster Distributions and Hadron Spectramentioning
confidence: 99%
“…a) Calculated average charged multiplicity versus total energy Q in e + e − annihilation events, in comparison with experimental data[45]. b) Momentum spectra of charged hadrons with respect to the variable ln(1/x), where x = 2E/Q, at Q = 34 GeV and Q = 91 GeV, confronted with distributions measured at PEP/PETRA and LEP[46].…”
mentioning
confidence: 99%
“…3 Therefore, it is necessary to account for the QED initial state corrections up to O(α 2 ) for precision measurements in the various energy regimes in e + e − annihilation having been explored so far and those which are planned to be investigated in the future, cf. [3][4][5][6][7][8][9][10][11][12]. For the corrections to the inclusive Born cross section σ(s), with s the center of mass (cms) energy squared, power corrections ∝ (m 2 e /s) k , k ≥ 1 can be safely disregarded.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that this description yields all but the power suppressed contributions in Refs. [18,19] comparing to the complete semi-analytic calculation [23] at O(α 2 s ) 5 . In this case the massive OMEs are formed between massless on-shell quark and gluon states.…”
Section: Introductionmentioning
confidence: 99%